If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3s-1=3-s+6
We move all terms to the left:
-3s-1-(3-s+6)=0
We add all the numbers together, and all the variables
-3s-(-1s+9)-1=0
We get rid of parentheses
-3s+1s-9-1=0
We add all the numbers together, and all the variables
-2s-10=0
We move all terms containing s to the left, all other terms to the right
-2s=10
s=10/-2
s=-5
| 7+3(r+1)=8+3r | | -6-7m=-5m | | 30−2x*x=−6 | | -6-7m=-5 | | x2+64=16x | | -4(7a+3)=-38-2a | | 2x-80=-160 | | -4,5x=27 | | 9j+8=j-8 | | -5+2t=-10 | | 10m+7=9m | | -6-7g=4-6g | | 2n=-6+n | | k8k=8 | | 5-(-x0)=-6 | | -3-3h=-6h | | 35d-25=5 | | 3(2x+1)=2(2x+9)-1 | | -2k=10-3k | | 2/x-2/2x=1/5 | | 3(n-5)+17=-4 | | m+10=-11 | | 2s=-9+3s | | k=+1220k=15 | | 3(x+8)=5x-2x+10 | | 5x=60-5× | | k+1220k=5 | | 2r+-3r+-15r=-19 | | 2x2-2x-12=0 | | 3{y-1}=2y-11 | | -16-f=5 | | 2a-a-1=18 |